1998
DOI: 10.1002/(sici)1521-186x(1998)19:2<112::aid-bem9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 50-Hz magnetic fields and ionizing radiation onc-jun andc-fos oncoproteins

Abstract: The effect of magnetic fields (50 Hz, 100 μTrms sinusoidal magnetic field combined with a 55 μT geomagnetic‐like field) and/or gamma rays of 60 Cobalt on the expression of the c‐jun and c‐fos proteins was investigated in primary rat tracheal epithelial cells and two related immortalized cell lines. Quite similar patterns and amplitudes of induction of these proteins were evidenced after either ionizing radiation or magnetic field exposure. No synergism after both treatments was observed. These findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Subsequently, other groups reported similar data from experiments in different cell systems, different MF signals, and different exposure regimens (Rao and Henderson 1996;Sauer et al 1997;Lagroye and Poncy 1998). On the contrary, Strasák et al (2009) reported that the expression of c-fos was not affected by low frequency MF at 2.0 mT and 50 Hz evaluating the level of proteins in brain mouse cells.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, other groups reported similar data from experiments in different cell systems, different MF signals, and different exposure regimens (Rao and Henderson 1996;Sauer et al 1997;Lagroye and Poncy 1998). On the contrary, Strasák et al (2009) reported that the expression of c-fos was not affected by low frequency MF at 2.0 mT and 50 Hz evaluating the level of proteins in brain mouse cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that extremely low frequency electromagnetic fields (ELF-EMFs) can exert influences on biological functions of cells and tissues. These effects include bone healing [Basset, 1983], nerve regeneration [Kim et al, 2002], influences on cell calcium levels [Walleczek et al, 1999] and oncogene activation [Lagroye and Poncy, 1998]. On the contrary, the most part of studies concerning genotoxic effects were negative [Vijayalaxmi and Obe, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…One investigation suggests that the stomach, as the most sensitive part of the gastrointestinal tract and the largest neuroendocrine organ in the body, is crucial for the initiation of a full stress response against all harmful stress [19]. Some paper reported that MF might alter transcription and translation, including hsp70 and immediate early response genes myc, jun and fos [20][21][22][23]. The increased expression of stress expression in the presence of MF suggests that the stress-sensitive gastrointestinal tract may response to MF as an environmental stress.…”
Section: Introductionmentioning
confidence: 78%